What factors should we modify to promote high functioning and prevent functional decline in people with schizophrenia? - Martínez-Cao, Clara; García-Fernández, Ainoa; González-Blanco, Leticia; Zurrón-Madera, Paula; Sáiz, Pilar A.; García-Portilla, María Paz; Bobes, Julio (Frontiers in Psychiatry, 2023)
Background: Since research in schizophrenia mainly focuses on deficits and risk factors, we need studies searching for high-functioning protective factors. Thus, our objective was to identify protective (PFs) and risk factors (RFs) separately associated with high (HF) and low functioning (LF) in patients with schizophrenia. Methods: We collected information (sociodemographic, clinical, psychopathological, cognitive, and functional) from 212 outpatients with schizophrenia. Patients were classified according to their functional level (PSP) as HF (PSP >70, n=30) and LF (PSP ≤50, n= 95). Statistical analysis consisted of Chi-square test, Student’s t-test, and logistic regression. Results: HF model: Variance explained: 38.4-68.8%; PF: years of education (OR=1.227). RFs: receiving a mental disability benefit (OR=0.062) and scores on positive (OR=0.719), negative-expression (OR=0.711), and negative-experiential symptoms (OR=0.822), and verbal learning (OR=0.866). LF model: Variance explained: 42.0-56.2%; PF: none; RFs: not working (OR=6.900), number of antipsychotics (OR=1.910), and scores on depressive (OR=1.212) and negative-experiential symptoms (OR=1.167). Conclusion: We identified specific protective and risk factors for high and low functioning in patients with schizophrenia and confirmed that high functioning factors are not necessarily the opposite of those associated with low functioning. Only negative experiential symptoms are a shared and inverse factor for high and low functioning. Mental health teams must be aware of protective and risk factors and try to enhance or reduce them, respectively, to help their patients improve or maintain their level of functioning.